2022
DOI: 10.1002/pmic.202200222
|View full text |Cite
|
Sign up to set email alerts
|

The use of pharmacological chaperones in rare diseases caused by reduced protein stability

Abstract: Rare diseases are most often caused by inherited genetic disorders that, after translation, will result in a protein with altered function. Decreased protein stability is the most frequent mechanism associated with a congenital pathogenic missense mutation and it implies the destabilization of the folded conformation in favour of unfolded or misfolded states. In the cellular context and when experimental data is available, a mutant protein with altered thermodynamic stability often also results in impaired hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 146 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Specifically, we envision that emerging high-throughput in silico [46][47][48][49] and in vitro 50 methods will be able to capture pathogenicity potential related to domain destabilization of all possible titin missense variants. Identification of these pathogenic variants is a prerequisite for the development of therapies able to counterbalance domain destabilization, including strategies based on exon skipping 51 or pharmacological chaperones 52 . Furthermore, considering the broad functions played by Ig proteins 22 , which indeed are the most common family in the human genome 53 , we propose that searching for hydrophilizing variants as we have done here could benefit management of a wide range of human conditions including other (cardio)myopathies 54,55 , cancer 56 and neurodegeneration 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we envision that emerging high-throughput in silico [46][47][48][49] and in vitro 50 methods will be able to capture pathogenicity potential related to domain destabilization of all possible titin missense variants. Identification of these pathogenic variants is a prerequisite for the development of therapies able to counterbalance domain destabilization, including strategies based on exon skipping 51 or pharmacological chaperones 52 . Furthermore, considering the broad functions played by Ig proteins 22 , which indeed are the most common family in the human genome 53 , we propose that searching for hydrophilizing variants as we have done here could benefit management of a wide range of human conditions including other (cardio)myopathies 54,55 , cancer 56 and neurodegeneration 57 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible therapeutic approach might be the identification of a PCNA stabilizing molecule. Such pharmaceutical chaperones continue gaining importance for the treatment of destabilizing missense mutations [76,77]. Due to the quantities of PCNA interaction partners [8,9], a stabilizer might interfere with the interaction of other binding partners.…”
Section: Pcna Stabilizing Molecules As Therapeutic Optionmentioning
confidence: 99%
“…This may result in the harmful buildup of protein aggregates, metabolites, or metabolic by‐products, potentially leading to the development of diseases. Research [6] has shown that over 40 different diseases that mainly impact the central nervous system are associated with repeat instability protein mutations, including β‐amyloid protein in Alzheimer's disease [7] and α‐synuclein protein in Parkinson's disease [8]. Therefore, enhancing the thermal stability of proteins is crucial for biomedical and industrial applications.…”
Section: Introductionmentioning
confidence: 99%